Fungal contamination of foods prepared in some hotels in the Kumasi metropolis - Darko, S. (2019)
There is an increase of food borne diseases in Ghana and therefore a lot of street food studies have been conducted in Kumasi, the Ashanti Region of Ghana with less information on microbiological safety of hotel foods. A total of forty food samples were aseptically collected from five highly patronised hotels (three star to budget). The hotels were selected by simple random sampling. Standard methods were used for the dilution, spreading, incubation, enumeration and identification. Serial dilution of each food was prepared in buffered peptone water and inoculated onto malt extract agar (MEA). Growth were counted and later identified. The bacterial counts were expressed to log10 cfu/g. Two foods from Hotel 01 (fresh pepper sauce and chicken and vegetable sauce) and six foods from Hotel 02 (chicken with noodles and vegetables, jollof rice, fried rice, potato chips, beef in vegetable sauce and coleslaw) were above the WHO acceptable levels (< 3 Log 10 cfu/g). Again, 4 foods from Hotel 03 (boiled plain rice, fish light soup, tossed mixed vegetables and tossed salad), Hotel 04 (vegetable sauce, fried chicken, mixed salad and fried rice) and Hotel 05 (goat light soup, fried chicken, fried rice and mixed vegetable salad) were all above the WHO acceptable levels. Fungi isolated were Eurotium herbariorum, Aureobasidium pullulans, Alternaria alternate, Botrytis cineria and Fusarium oxysporu. It was observed that foods tested were above the acceptable levels and could be sources of food borne pathogens. The causes could be attributed to poor food hygiene and inadequate processing. It is recommended that hotel inspections should include microbial test on foods.